KEWENANGAN PEMERINTAH DAERAH DALAM PENYELENGGARAAN PERIZINAN BERUSAHA - Moh Rizky A Jumadil; Rahmat Setiawan; Mustating Daeng Maroa; Asis Harianto; M. Ikhwan Rays (Jurnal Yustisiabel, 2023)
The authority to administer business licenses in the regions and the authority of the regional government in administering business licenses using the Online Single Submission (OSS) system are matters that will be studied. The research method used is normative legal research. The results of the research and discussion show that the authority to administer business licenses in the regions is a concurrent authority owned by the regions. Where the authority of the regional government must follow the norms, standards, criteria and procedures set by the central government. The implementation of Business Licensing in the Regions is carried out to improve the investment ecosystem. The improvement of the investment ecosystem and business activities includes Risk-Based Business Licensing, basic requirements for Business Licensing, and sector Business Permits and ease of investment requirements. The implementation of Business Licensing using the Online Single Submission (OSS) System by the regional government is limited to operating the system while the Central Government through the OSS institution carries out the implementation. The OSS system does not mean taking over the authority of the regional government in the licensing process, because the regional government continues to oversee investors' commitment to business licensing.